2015
DOI: 10.1063/1.4907224
|View full text |Cite
|
Sign up to set email alerts
|

Electrically charged dispersions of ferroelectric nanoparticles

Abstract: International audienceno abstrac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The presence of larger particles may interfere with the homogeneity of the liquid crystal, and thus destroy the orientation of the LC molecules, while the smaller particles lose their ferroelectric properties [7]. Previous work [9,10,[13][14][15][16] has shown that the preparation of ferroelectric nanoparticles is a difficult process. In recent years, one found new processes for the production of BaTiO 3 ferroelectric nanoparticles, including sol-gel method, hydrothermal method, molten salt method, mechanochemical synthesis or combustion synthesis [17,18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of larger particles may interfere with the homogeneity of the liquid crystal, and thus destroy the orientation of the LC molecules, while the smaller particles lose their ferroelectric properties [7]. Previous work [9,10,[13][14][15][16] has shown that the preparation of ferroelectric nanoparticles is a difficult process. In recent years, one found new processes for the production of BaTiO 3 ferroelectric nanoparticles, including sol-gel method, hydrothermal method, molten salt method, mechanochemical synthesis or combustion synthesis [17,18].…”
Section: Methodsmentioning
confidence: 99%
“…This dipole-dipole interaction may provide to an increase of the order parameter of LC and thus the dielectric anisotropy and birefringence of the ferroelectric LC suspension. However, the nature of interactions are clearly more complex, as for example, the nps are likely to be charged as well, as recently demonstrated [9].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, nanophysics of liquid crystals are a rapidly expanding field of soft matter science for the fascinating fundamental and technological perspectives [6]. Burylov and Zakhlevnykh studied the conditions of existence of different orientational states for a suspension of ferromagnetic particles in nematic liquid crystals, in an external magnetic field [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the nanoparticle aggregation and percolation phenomena, possible effects of charge generation by nanoparticles subjected to the high electric field should be taken into account to ensure the correct interpretation of the experimental data. 34 For example, these factors could be among possible reasons for the observed increase in the electrical conductivity of the system "nematic liquid crystalSn 2 P 2 S 6 ." 35 According to Ref.…”
mentioning
confidence: 99%